PERANCANGAN BASIS DATA OPEN TRIP PENDAKIAN GUNUNG PADA SUKATRAVELER.ID DENGAN METODE DBLC - Fajar, Muhammad Adita; Afifah, Silviani; Nugraha, Bintang Kusuma Setya; Sari, Ika Novita; Sakinah, Aprillia; Ariq, Muhammad Rafif Fadhlurrahman (Jurnal Ilmiah Sistem Informasi, 2024)
Mountains on the island of Java have very beautiful views and attract many domestic and foreign tourists. This is an opportunity for the welfare of the people in the mountain environment and the country, to increase state income. As time goes by, many people, both young and old, are interested in and appreciate mountain climbing. Maybe as a society we are still amateurs and don't know how to choose the right equipment for traveling. That's why we need a system that allows even beginners to easily register and rent items, and recognize what's in your bag. This research uses methods to overcome difficulties in identifying items in bags for beginners and difficulties in carrying large amounts of items for climbers themselves. This research includes several steps: problem formulation, data collection, and providing rental equipment to climbers. “ID climbed Mount Merbabu, Central Java